2012
DOI: 10.1111/jocn.12003
|View full text |Cite
|
Sign up to set email alerts
|

‘Sustaining Place’ – a grounded theory of how informal carers of people with dementia manage alterations to relationships within their social worlds

Abstract: 'Sustaining Place' facilitates enhanced understanding of the complex and socially situated nature of informal dementia care through its portrayal of informal carers as social agents and can be used to guide nurses to better support those who live with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 54 publications
4
33
0
Order By: Relevance
“…A paper by Haley, Levine, Brown, and Bartolucci (1987) reported that those caregivers with a larger number of friends and social contacts, as well as those carers who attended more social activities with friends had an increased overall life satisfaction. A more recent study conducted by Daly, McCarron, Higgins, and McCallion (2013) demonstrates how informal carers use social networks as a way to manage and sustain their changing role as carer.…”
Section: Resultsmentioning
confidence: 99%
“…A paper by Haley, Levine, Brown, and Bartolucci (1987) reported that those caregivers with a larger number of friends and social contacts, as well as those carers who attended more social activities with friends had an increased overall life satisfaction. A more recent study conducted by Daly, McCarron, Higgins, and McCallion (2013) demonstrates how informal carers use social networks as a way to manage and sustain their changing role as carer.…”
Section: Resultsmentioning
confidence: 99%
“…These examples suggest that dementia cafés have the potential to be seen as a ‘sustaining place’ [13] providing valued support even after the caring role has ended. This is particularly important as although the caring role can be difficult, the end of caring can require a long period of adjustment [25] and carers may benefit from the support of places such as dementia cafés.…”
Section: Discussionmentioning
confidence: 99%
“…Social isolation [11] can be particularly important as carers often may not want to leave the person they care for and can be reluctant to go out because of changes in their behaviour [12]. Furthermore, people living with dementia and their carers report both experiencing stigma once diagnosed [13] and reduced social support [11]. Despite this, increasingly, with reductions in services, carers are expected to rely on their social networks for support [14].…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers identified loss of their community and friends as another painful result of dementia-related changes. Caregivers found that friends often abandoned them and that their community dwindled to only a few devoted individuals (Daly, McCarron, Higgins, & McCallion, 2013;Sanders et al, 2008): "I am a lone soldier in the battleground, all others have long deserted the field" (Mayer, 2001, p. 55). Caregivers limited dining with friends (an important social event across cultures) because eating with company often revealed the behavioral symptoms of dementia or was simply messy (Gillies, 2012;.…”
Section: Reciprocal Synthesismentioning
confidence: 99%